Educational practices in mathematics from social and political perspectives. Comprehensive Sex Education and Human Rights as learning environments and as research settings (Praxis Educativa, 2016)
The sense of teaching mathematics in secondary schools from human rights, citizenship and comprehensive sex education responds to the interest in understanding the curriculum as a political project that addresses the teaching of disciplines in favor of curricular justice. This perspective aims to strengthen the positions of Critical Mathematics Education that point to the need and complexity of establishing more explicit connections between mathematics, education and democracy. In this article we offer the proposal of a university course that addresses the practices of teachers, assistantships, and the development of proposals for mathematics education in human rights (citizenship) and comprehensive sex education that have been real educational settings –areas where inclusive subjectivities are constituted– and powerful learning environments, seen as spatialities built by power– knowledge relations.
Keywords: mathematics criticism; learning environments; educational settings; citizenship; comprehensive sex education